2021
DOI: 10.1002/cmdc.202100306
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chameleonic Efficiency

Abstract: Chameleonic properties, i. e., the capacity of a molecule to hide polarity in non-polar environments and expose it in water, help achieving sufficient permeability and solubility for drug molecules with high MW. We present models of experimental measures of polarity for a set of 24 FDA approved drugs (MW 405-1113) and one PROTAC (MW 1034). Conformational ensembles in aqueous and non-polar environments were generated using molecular dynamics. A linear regression model that predicts chromatographic apparent pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Indeed, it has been shown previously that the cross-sectional area threshold of 80 Å 2 is critical to tip the balance toward passive diffusion being high enough to effectively shorten the membrane residence time of drug molecules, below which efflux pumps can readily pick up the molecules from the membrane. ,, This property has recently been termed “molecular chameleonicity” and can afford higher than expected permeability for PROTACs and other bRo5 compounds . Drug design teams seeking to incorporate chameleonic properties may benefit by studying the behavior of their compounds in both aqueous and non-polar solvent environments; the parameter of “chameleonic efficiency” has been proposed for this purpose . Another useful tool in the analysis of permeability for bRo5 molecules is the experimental polar surface area (EPSA) method, a chromatographic technique developed by Pfizer for the analysis of intramolecular hydrogen bonding .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown previously that the cross-sectional area threshold of 80 Å 2 is critical to tip the balance toward passive diffusion being high enough to effectively shorten the membrane residence time of drug molecules, below which efflux pumps can readily pick up the molecules from the membrane. ,, This property has recently been termed “molecular chameleonicity” and can afford higher than expected permeability for PROTACs and other bRo5 compounds . Drug design teams seeking to incorporate chameleonic properties may benefit by studying the behavior of their compounds in both aqueous and non-polar solvent environments; the parameter of “chameleonic efficiency” has been proposed for this purpose . Another useful tool in the analysis of permeability for bRo5 molecules is the experimental polar surface area (EPSA) method, a chromatographic technique developed by Pfizer for the analysis of intramolecular hydrogen bonding .…”
Section: Resultsmentioning
confidence: 99%
“…43 Drug design teams seeking to incorporate chameleonic properties may benefit by studying the behavior of their compounds in both aqueous and non-polar solvent environments; the parameter of "chameleonic efficiency" has been proposed for this purpose. 44 Another useful tool in the analysis of permeability for bRo5 molecules is the experimental polar surface area (EPSA) method, a chromatographic technique developed by Pfizer for the analysis of intramolecular hydrogen bonding. 45 The EPSA technique has been successfully applied for the optimization of compounds with permeability challenges, including peptides 46 and other large, polar molecules.…”
Section: Resultsmentioning
confidence: 99%
“…34 In this context, design of PROTAC molecules with a “chameleonic behavior”, thus the capacity of a molecule to hide polarity in non-polar environments and expose it in water, is an interesting strategy which can take advantage of predictive computational methods, such as molecular dynamics. 35 Additional strategies for the design of PROTACs with improved cell membrane penetration employ shielding of polar groups by bulky non-polar moieties 36 or replacement of an amide functionality for an ester. 37 Recently, a method combining parallel artificial membrane permeability assay (PAMPA) and lipophilic permeability efficiency (LPE) has been developed in order to better understand how structural elements of VHL based PROTACs influence compound permeability.…”
Section: Probing the Degradation Pathwaymentioning
confidence: 99%
“…Furthermore, the experimental alkane/water and toluene/water partition systems have given insights into the 'chameleonic' properties of drugs whose chemical space is beyond of the metrics of the rule-of-five, although experimental limitations that fall on the low solubility of compounds in alkane-type solvents may limit their application [26][27][28]. As an example, it has been shown that macrocyclic drugs populate significantly less polar and more compact conformational ensembles in an apolar than in a polar environment, which enables to balance aqueous solubility and cell permeability [22].…”
Section: Introductionmentioning
confidence: 99%